Effect of season, number of service and station on conception rate and calf sex for dairy cow in sulaimania region: 1Faraidoon, A. M, Amin, 1Talib, G. M. Ali, 2Burhan, S. Muhammad and 2Sherawan, A. Muhammad - Amin, Faraidoon A. M (The Iraqi Journal of Veterinary Medicine, 2014)
The objective of the present study was to evaluate the effect of season and first, second and third services on reproductive efficiency of 1086 cows throughout the artificial insemination technique during 2012 as well as the effect of season of the year on the conception rates in cows in Sulaimani Region. The conception rate of first, second and third services were 69.3, 27.5, and 3%, respectively, with overall conception rate 45%. The total number of male calves born was 282 and the female calves were 211. The conception rate obtained at the Halabja station reaching its highest value follow Sharazoor station then Chamchamal station, while Rania station performed the lowest value. The conception rate in the Sharazoor station at the spring months reaching its highest value follow at the winter months then at the autumn months, while at the summer months performed lowest value. The results of the this work is concluded that a good season of fertility of the cows of Halabja is in winter to summer months, while in Sharazoor and Rania the fertility is better in winter to spring and in Chamchamal the good seasons of fertility are relatively similar.